Retroviral RNA identified in the cerebrospinal fluids and brains of individuals with schizophrenia - Karlsson, Håkan; Bachmann, Silke; Schröder, Johannes; McArthur, Justin C.; Torrey, Edwin F.; Yolken, Robert H. (Proceedings of the National Academy of Sciences of the United States of America, 2001)
Schizophrenia is a serious brain disease of uncertain etiology. A role for retroviruses in the etiopathogenesis of some cases of schizophrenia has been postulated on the basis of clinical and epidemiological observations. We found sequences homologous to retroviral pol genes in the cell-free cerebrospinal fluids (CSFs) of 10 of 35 (29%) individuals with recent-onset schizophrenia or schizoaffective disorder. Retroviral sequences also were identified in the CSFs of 1 of 20 individuals with chronic schizophrenia. However, retroviral sequences were not identified in any of the CSFs obtained from 22 individuals with noninflammatory neurological diseases or from 30 individuals without evidence of neurological or psychiatric diseases (χ2 = 19.25, P < 0.001). The nucleotide sequences identified in the CSFs of the individuals with schizophrenia or schizoaffective disorder were related to those of the human endogenous retroviral (HERV)-W family of endogenous retroviruses and to other retroviruses in the murine leukemia virus genus. Transcription of RNA homologous to members of the HERV-W family of retroviruses also was found to be up-regulated differentially in the frontal cortex regions of brains obtained postmortem from individuals with schizophrenia, as compared with corresponding tissue from individuals without psychiatric diseases. The transcriptional activation of certain retroviral elements within the central nervous system may be associated with the development of schizophrenia in at least some individuals. The further characterization of retroviral elements within the central nervous system of individuals with schizophrenia might lead to improved methods for the diagnosis and management of this disorder.